Petrol station and disabled customers - Rymsza, Barbara; Kacperczak, Krzysztof (Przegląd Komunikacyjny)
The article is devoted to the problem of accessibility of petrol stations for people with disabilities. In a cross-sectional way it describes the problems of disabled people using all the functions offered by a petrol station, focusing on one - which is neglected in the author's opinion - the problem of refueling a vehicle. It describes the unacceptable current situation and possible ways of improvement. Keywords: Roads; Petrol stations; Disabled